Bridging the demand and supply gap in community tourism - Paul Nkemngu Acha-anyi (African Journal of Hospitality, Tourism and Leisure, 2015)

(untitled)
While the benefits of sustainable tourism such as job creation, income generation and improved quality of life have often attracted many communities to invest in tourism development, frustration generally sets in when the anticipated benefits fail to materialise. Many townships in South Africa can identify with this situation as the success stories of townships such as SOWETO and Khayelitsha have not been successfully replicated in their communities. The purpose of this study is to explore ways of bridging the demand and supply divide as a strategy in the implementation of sustainable community tourism in townships, particularly in the Soshanguve township north of City of Tshwane. The study employs the quantitative methodology in collecting two sets of data; one on visitors (demand-side) expectations of township tourism and the other survey on residents perceptions on the strengths and weaknesses of the Soshanguve township product offering (supply environment). An analysis of the two sets of data reveals both similarities and gaps between the demand-side expectations of township tourism and the Soshanguve township product and supply environment. The recommendations from this study emphasis the importance of incorporating visitors expectations in the tourism development strategy but more importantly, ensuring that the full range of the township product offering is effectively communicated to potential visitors. This is necessary because South African townships are generally misconstrued to offer homogenous heritage and cultural products.